(untitled) (Itinera, 2019)
The dramaturgical principle of montage has a crucial importance in the mechanism of transposition from the novel to the staging and also includes the operations of quotation and translation. Heiner Müller’s transposition of the Liaisons dangereuses by Choderlos de Laclos into the pièce Quartett is an exemplary case for studying these dynamics, as well as the staging by Valter Malosti. Montage, Malosti, Heiner Müller, translation.